Beyond Turk and Hindu: Rethinking Religious Identities in Islamic South Asia by David Gilmartin and Bruce B. Lawrence, eds. (Gainsville: University Press of Florida, 2000. 354 pages.) (American Journal of Islam and Society, 2002)
Beyond Turk and Hindu grew out of a collection of papers presented at a conferenceon "Islam in South Asia," held at Duke University in April 1995. Ithas 3 sections, 13 chapters, 8 photographs, 3 maps, 2 tables, a glossary, andan index. The book deals with the broad subject of civilizational interfaces inthe South Asian context. It belongs to the category of interfaith relations andis addressed to a general audience interested in the Hindu-Muslim dialectic.The authors do not accept the premise that interreligious differences inSouth Asia are set and irreconcilable. To quote the editor: "We vigorouslycontend that there is a larger point to make, namely, that the constant interplayand overlap between Islamic and Indic worldviews may be at least aspervasive as the Muslim-Hindu conflict ... " This position is a challenge tothose scholars who view India and Pakistan as embodiments of two separatereligious identities.Section One contains three essays on textual analysis to assess the samenessand otherness of identity formation. The authors do not avoid the controversiesthat are bound to emerge from the sometimes disparaging tennsused by Hindus and Muslims to refer to each other, or the animosities thathave emerged from the desecration of mosques and temples:Arabic and Persian use of the term Hindu had a range of meanings thatchanged over time, sometimes denoting an ethnic or geographic referentwithout religious content. Similarly, Indic texts referring to the invadersfrom the northwest used a variety of terms in different contexts, includingyavanas, m/ecchas,farangis, musafmans, and Turks. These terms sometimescarried a strong negative connotation, but they rarely denoted a distinctreligious community conceived in opposition to Hindus. In and ofthemselves, however, such terms tell us little. To understand the usage ofthese terms, one must move beyond the terminology itself- beyond Turkand Hindu - to analyze the framing categories and generic contexts withinwhich these terms are used.The authors illustrate the power of bidirectional cultural forces by offeringthe example of the Punjab's Bulle Shah and Bengal's mystical Satya Pir.Bulle Shah, a contemporary of Shah Waliullah of Delhi, lived in the late ...